Maintenance of genetic variation and moderate differentiation among populations under sex-biased dispersal in the common vole Microtus arvalis in patchy habitats - Borkowska, Anetta; Ratkiewicz, Miroslaw; Jaarola, Maarit (ACTA THERIOLOGICA, 2010)
We present a microgeographic analysis of 34 allozyme loci and the control region of mitochondrial DNA (mtDNA) in the common vole Microtus arvalis (Pallas, 1779), performed to assess the effects of environmental heterogeneity on the distribution of genetic variation among populations in the Biebrza river valley, NE Poland The common vole occurs there in two types of habitat open grassland and pastures around the valley (GP populations), and abandoned fields on small hills isolated by wetlands (SH populations) No significant genetic differences were found between SH and GP populations with respect to allelic richness, nor average observed and expected heterozygosities The average genetic differentiation at allozyme loci among the SH populations was significantly lower (F-ST = 0 066) than among the GP populations located around the Biebrza valley (F-ST = 0 112), and an isolation by distance pattern was detected (r = 0 26, p < 0 05) Mitochondrial DNA differentiation among the GP populations was great (F-ST, = 0 357, p < 0 01), indicating that female dispersal was 4 4-6 5 times lower than for males Our results and reviewed published data on M arvalis dispersal suggest that common vole dispersal in patchy natural and semi-natural habitats is male-biased and could generate moderate population divergence, with relatively high levels of genetic variation retained within populations